Small-Angle X-ray Scattering Models of APOBEC3B Catalytic Domain in a Complex with a Single-Stranded DNA Inhibitor - Barzak FM; Ryan TM; Kvach MV; Kurup HM; Aihara H; Harris RS; Filichev VV; Harjes E; Jameson GB (MDPI (Basel, Switzerland), 2021)
In normal cells APOBEC3 (A3A-A3H) enzymes as part of the innate immune system deaminate cytosine to uracil on single-stranded DNA (ssDNA) to scramble DNA in order to give protection against a range of exogenous retroviruses, DNA-based parasites, and endogenous retroelements. However, some viruses and cancer cells use these enzymes, especially A3A and A3B, to escape the adaptive immune response and thereby lead to the evolution of drug resistance. We have synthesized first-in-class inhibitors featuring modified ssDNA. We present models based on small-angle X-ray scattering (SAXS) data that (1) confirm that the mode of binding of inhibitor to an active A3B C-terminal domain construct in the solution state is the same as the mode of binding substrate to inactive mutants of A3A and A3B revealed in X-ray crystal structures and (2) give insight into the disulfide-linked inactive dimer formed under the oxidizing conditions of purification.
Keywords: APOBEC; APOBEC inhibitors; APOBEC3; APOBEC3B; SAXS; cancer evolution; dimer; drug resistance; virus restriction; Catalytic Domain; Cytidine Deaminase; DNA, Single-Stranded; Dimerization; Humans; Minor Histocompatibility Antigens; Mutation; RNA, Viral; Retroviridae; Retroviridae Infections; Scattering, Small Angle